2006
DOI: 10.1007/s10681-006-7399-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening techniques and sources of resistance against parasitic weeds in grain legumes

Abstract: A number of parasitic plants have become weeds, posing severe constraints to major crops including grain legumes. Breeding for resistance is acknowledged as the major component of an integrated control strategy. However, resistance against most parasitic weeds is difficult to access, scarce, of complex nature and of low heritability, making breeding for resistance a difficult task. As an exception, resistance against Striga gesnerioides based on a single gene has been identified in cowpea and widely exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 58 publications
1
124
0
3
Order By: Relevance
“…The results are in agreement with other reports which show wide availability in resistant genotypes against A. vogelii (Mainjeni, 1999;Kabambe et al, 2008a, Mbwaga et al, 2000Riches, 1989Riches, , 2001Rubiales et al, 2006;Omoigui, 2012). The results also generally showed that A. vogelii is naturally more prevalent in the mid-altitude sites where all entries are better adapted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results are in agreement with other reports which show wide availability in resistant genotypes against A. vogelii (Mainjeni, 1999;Kabambe et al, 2008a, Mbwaga et al, 2000Riches, 1989Riches, , 2001Rubiales et al, 2006;Omoigui, 2012). The results also generally showed that A. vogelii is naturally more prevalent in the mid-altitude sites where all entries are better adapted.…”
Section: Discussionsupporting
confidence: 92%
“…The witchweed A. vogelii may be controlled through trap crops such as dolichos bean (Lablab purpureus [L.] Sweet) cotton (Gossypium hirsutum L.), okra (Hibiscus esculentus L.), sunflower (Helianthus annuus L.) pea (Pisum sativum L.) and faba bean (Vicia faba L.) (Parker and Riches, 1993). There is generally greater availability of resistant genotypes against A. vogelii (Riches, 2001;Mainjeni, 1999;Rubiales et al, 2006;Omoigui, 2012). Thus, production is threatened by A. vogelii and screening for resistance among existing legumes crops or varieties can help to avoid working with the most susceptible varieties.…”
Section: Introductionmentioning
confidence: 99%
“…In infested field, several criteria have been used by authors to quantify resistance to orobanche infestation (Rubiales et al, 2006;Abbes et al, 2007a). The best index is the number of orobanche shoots per host plant, which gives the most reliable estimation of the total infestation level (Rubiales et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In small millets, early studies towards germplasm characterization and breeding for crop improvement for agronomic traits have not been coupled with the investigation and assessment of the genetic variants for Striga resistance. Hence, characterization of the resistance mechanisms usually follows the identification of resistance sources (Rubiales et al, 2006).…”
Section: Nature and Genetic Basis Of Resistancementioning
confidence: 99%